The Function of Zinc in Animal, Plant, and Human Nutrition - Ozturk, Hamidullah; Niazi, Parwiz; Mansoor, Mujibullah; Monib, Abdul Wahid; Alikhail, Mirwais; Azizi, Azizaqa (Journal for Research in Applied Sciences and Biotechnology, 2023)
Zinc is a crucial micronutrient found in food that is essential for the development of all living organisms, it plays a vital role in gene expression and various physical processes, its deficiency can lead to disease onset and reduce crop yield, restrict plant development, and lower the quality of produced goods, zinc is also used in fertilizers and the handling of metals to protect them from oxidation. Additionally, Zinc is important in enhancing the human immune system, and its deficiency can result in hair loss, memory loss, skin disorders, and muscular weakness.